PEMAHAMAN SISWA TENTANG MANAJEMEN KARIR PASCA LAYANAN INFORMASI KARIR DI MAN 2 BATUSANGKAR - Wahyuni, Roza Sri; Yuliani, Tri (PRODU-Prokurasi Edukasi (Jurnal Manajemen Pendidikan Islam), 2020)
This study aims to determine students' understanding of career selection after obtaining information services including career selection on sub-variables of motivation, knowledge, personality, abilities. One of the uses of the results of this study is as information for students, lecturers, teachers, students, and readers on how students' understanding of career selection in MAN 2 Batusangkar. The research method used in this study is the method of "Field Research" (field research) that is descriptive quantitative. The population in this study were students of class XII MAN 2 Batusangkar, totaling 256 people. The sample in this study were all students of class XII IS 1, amounting to 31 people in MAN 2 Batusangkar. The results showed that the understanding of students of class XII MAN 2 Batusangkar about career selection most students understood that the career would be continued at the College or Occupation and there were still a few who understood enough about the motivational factors that were lacking from individuals to choose the career they would choose for the future